PEMBERDAYAAN MASYARAKAT DESA MALIAYA MELALUI PROGRAM KKN UNIVERSITAS MUHAMMADIYAH MAMUJU: INTEGRASI NILAI SPIRITUAL DAN EKOLOGIS DALAM BIDANG SOSIAL, PERTANIAN, DAN PENDIDIKAN - Kurnia, Kurnia; Abdul Wahab ,; Indriani , Indriani (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
The Community Service Programme (KKN) was a form of student engagement with society that integrated academic knowledge with social involvement. This article aimed to describe the implementation and outcomes of the KKN programme by the University of Muhammadiyah Mamuju (4th batch) in Maliaya Village, Malunda District, Majene Regency. A participatory approach was applied through counselling, training, and community assistance. The programme focused on three areas: (1) social, through waste management education and public facility cleaning; (2) agriculture, through training on organic planting media; and (3) education, through elementary school teaching and leadership training for junior high school students. The results showed improved public awareness and participation, along with enhanced student problem-solving and leadership skills. This activity had a positive impact on both the local community and students as future leaders